Lessons From Placing an Observer on Commercial Cargo Ships Off the U.S. West Coast: Utility as an Observation Platform and Insight Into Ship Strike Vulnerability - Flynn, Kiirsten Regina; Calambokidis, John (Frontiers in Marine Science, 2019)
Ship strikes of whales are a growing concern around the world and especially along the U.S. West Coast, home to some of busiest ports in the world and where ship strikes on a number of species including blue, fin, and humpback whales have been documented. This trial program examined the feasibility, logistics, industry cooperation, and effectiveness of placing an observer on board a commercial ship. An experienced marine mammal observer went on five voyages, spanning over eight days on ships operating between U.S. West Coast ports. Daylight observations were conducted over 68hrs and covered over 1300nm as ships transited between three ports (Seattle, Oakland, and LA/Long Beach(LA/LB)). Sightings of large whales were reported on all (n=42), totaling an estimated 57 individuals that included humpback, blue, fin and beaked whales. Close encounters of large whales occurred, (on one occasion a near miss, estimated at 40m, of two humpbacks) and on another, a ship chose to alter course to avoid whale sightings in its path identified by the observer. All ships personnel cooperated and voluntarily aided in the observations even after initial skepticism by some crew about the program. While most effort on mitigating ship strikes along the U.S. West Coast has focused on shipping lanes, the vast majority of these sightings occurred outside these lanes and on the transit routes, emphasizing the need for added attention to these areas. This experiment demonstrates the effectiveness and promise of observations from ships providing critical information on whale locations at risk to ship strikes.